2016
DOI: 10.1007/s15010-016-0914-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the diagnostic value of MRI and 18F-FDG-PET/CT in suspected spondylodiscitis

Abstract: PurposeThe purpose of this study was to evaluate the diagnostic value of 18F-fluorodeoxyglucose (FDG) positron emission tomography and computed tomography (PET/CT scan) and magnetic resonance imaging (MRI) in diagnosing spondylodiscitis and its complications, such as epidural and paraspinal abscesses.MethodsFrom January 2006 to August 2013 patients with a clinical suspicion of spondylodiscitis, with an infection, or with fever of unknown origin were retrospectively included if 18F-FDG-PET/CT and MRI of the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 28 publications
3
70
0
4
Order By: Relevance
“…These examples highlight the potential role of 18 F-FDG PET/CT, not just for diagnosis, but also as an effective means of monitoring the progress of spinal infection in the context of previous EVAR, or indeed metallic spinal instrumentation that may preclude accurate assessment by MRI. This is supported by several studies that have shown 18 F-FDG PET/CT to be at least equivalent to MRI in diagnosing spondylodiscitis and may be used as a means of monitoring the response to treatment [3337]. In the absence of PET/CT facilities, other nuclear medicine modalities including 99m Tc-MDP bone scan and Gallium scan (particularly when combined with single photon emission computed tomography (SPECT)/CT) have also been shown to be viable alternatives for the detection of spondylodiscitis [38, 39].…”
Section: Discussionmentioning
confidence: 64%
“…These examples highlight the potential role of 18 F-FDG PET/CT, not just for diagnosis, but also as an effective means of monitoring the progress of spinal infection in the context of previous EVAR, or indeed metallic spinal instrumentation that may preclude accurate assessment by MRI. This is supported by several studies that have shown 18 F-FDG PET/CT to be at least equivalent to MRI in diagnosing spondylodiscitis and may be used as a means of monitoring the response to treatment [3337]. In the absence of PET/CT facilities, other nuclear medicine modalities including 99m Tc-MDP bone scan and Gallium scan (particularly when combined with single photon emission computed tomography (SPECT)/CT) have also been shown to be viable alternatives for the detection of spondylodiscitis [38, 39].…”
Section: Discussionmentioning
confidence: 64%
“…Fluorine-18 fluorodeoxyglucose positron emission tomography/CT ( 18 F-FDG-PET-CT) is a procedure well known in oncology and infectious diseases and appears to be playing an increasingly important role in the diagnosis of spondylodiscitis (18,19,34). PET-CT represents a good alternative particularly in the case of contraindications to contrast-enhanced MRI/CT (e.g., kidney failure).…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Fluorodeoxyglucose‐positron emission tomography combined with X‐ray computed tomography (FDG‐PET/CT) imaging has been used for many years as an effective method to stage and restage malignancies . Several studies have demonstrated high sensitivity of FDG‐PET/CT for diagnosis of infection of prosthetic devices, osteomyelitis and determining the aetiology of pyrexia of unknown origin (PUO) . Small studies have also demonstrated high clinical impact of FDG‐PET/CT in patients with neutropenic fever (NF) of unclear cause, with benefits of de‐escalating or rationalising antimicrobials, of directing further investigation such as bronchoscopy or tissue sampling and establishing an aetiological diagnosis of NF .…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies have demonstrated high sensitivity of FDG-PET/ CT for diagnosis of infection of prosthetic devices, osteomyelitis and determining the aetiology of pyrexia of unknown origin (PUO). [2][3][4] Small studies have also demonstrated high clinical impact of FDG-PET/CT in patients with neutropenic fever (NF) of unclear cause, with benefits of de-escalating or rationalising antimicrobials, of directing further investigation such as bronchoscopy or tissue sampling and establishing an aetiological diagnosis of NF. 5,6 There is emerging evidence that FDG-PET/CT is more sensitive for invasive fungal infection (IFI), its dissemination and response to therapy compared to traditional computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%